Resistance-Associated Amino Acid Variants Associated with Boceprevir plus Pegylated Interferon-α2B and Ribavirin in Patients with Chronic Hepatitis C in the Sprint-1 Trial. Issue 3 (April 2013) - Ogert, Robert A; Howe, John A; Vierling, John M; Kwo, Paul Y; Lawitz, Eric J; McCone, Jonathan; Schiff, Eugene R; Pound, David; Davis, Mitchell N; Gordon, Stuart C; Ravendhran, Natarajan; Rossaro, Lorenzo; et al.
Background: Resistance to direct-acting antivirals represents a new challenge in the treatment of chronic hepatitis C. Methods: SPRINT-1 was a randomized study of treatment-naive patients with genotype (G) 1 hepatitis C infection ( n =595) that evaluated the safety and efficacy of boceprevir (BOC) when added to pegylated interferon-α2b plus ribavirin (PR). Plasma samples collected at protocol-specified visits were analysed by population sequencing for detection of BOC-associated resistance-associated variants (RAVs). Results: A total of 17/24 (71%) patients randomized to BOC with baseline RAVs achieved sustained virological response (SVR). V55A/I ( n =14), Q41H ( n =11) and T54S ( n =9) were the most frequently detected polymorphisms at baseline. Seven non-SVR patients with baseline RAVs had V55A (relapse, n =3; breakthrough, n =1; and non-response, n =1) and/or R155K (non-response, n =2). In total, 63/144 (44%) patients with sequenced post-baseline samples (2 SVR, 61 non-SVR) had detectable RAVs after BOC treatment (G1a: R155K [39/49; 80%], V36M [37/49; 76%] and T54S [24/49; 49%]; G1b: T54S [3/11; 27%], T54A [4/11; 35%], A156S [2/11; 18%] and V170A [2/11; 18%]). RAV frequency varied according to the virological response: 90%, 67%, 27% and 37% of breakthrough, incomplete virological response, relapse and non-responder patients, respectively, had post-baseline RAVs present. Similar RAVs were identified in both the PR lead-in and no-lead-in arms and the frequency of post-baseline RAVs was highest in the low-dose ribavirin arm. Conclusions: SVR rates were not compromised among patients with RAVs at baseline; however, a lower starting mg/kg dose of ribavirin was associated with a higher frequency of post-baseline RAVs.